VehLoc: an in-vehicle high-precision location method based on BLE multi-channel RSSI values - Ze ZHAO; Yuan GAO; Li CUI (Tongxin xuebao, 2018)
High precision in-vehicle positioning is the basis of providing smart in-vehicle service, passengers' behavior analysis and other issues, and has important practical value. The RSSI (received signal strength indicator) values of BLE (bluetooth low energy) can be used to do analysis and computation in location system. To deal with the problem that RSSI is vulnerable to environmental issues, an in-vehicle location method called VehLoc based on BLE multi-channel multi-RSSI values was proposed. By using a plurality of Bluetooth transmitters, the location of the receiving terminals in the vehicle was analyzed by combining the coarse, fine classifier and distribution fitting of the user's RSSI values in different channels. The experimental results show that the average accuracy of VehLoc in the five main positions in-vehicle classification can reach 90%.